Pengaruh Perhatian Orang Tua dan Minat Belajar Siswa Pada Pembelajaran Daring Terhadap Hasil Belajar Matematika Kelas V SD Negeri Mangunrekso 01 - Pujiningrum, Erlina; Siswanto, Joko; Sukamto, Sukamto (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
The background of this research is the lack of interest in learning mathematics, especially with the online learning of teachers do not explain the material to students. In addition, parents do not pay attention to children's learning activities at home because most of them are busy working outside the city. This causes students to pay less attention to the learning process because the students do not get attention from their parents and the interest in learning students is also lacking so that the learning outcomes are low. The problem in this study is 1) Is there any influence of parents' attention on online learning on the results of learning mathematics?, 2) Is there an influence of students' interest in online learning on the results of mathematics learning?, 3) Is there an influence of parents' attention and interest in learning students in online learning together on the results of learning mathematics? The purpose of this study was to find out the influence of parents' attention and students' interest in online learning on the results of learning mathematics grade V SD Negeri Mangunrekso 01. This type of research is quantitative with ex post facto method. The research population is all students of SD Negeri Mangunrekso 01. The samples were 29 grade V students using purposive sampling techniques. The data in this study was obtained through questionnaires, interviews, and documentation. The results showed that parents' attention to online learning has no significant effect on math learning outcomes because the score is significant 0.234 > 0.05, if the attention of parents increases by one unit then the results of learning mathematics will increase by 9,4%. There is asignificant influence on students' learning on online learning outcomes. This is evidenced by a significant value of 0.026 < 0.05. Then there is the influence of parents' attention and interest in learning students in online learning together on the results of learning mathematics grade V SD Negeri Mangunrekso 01 with a significance score of 0.006 < 0.05 and its influence of 32,5%.